Environmental Determinants of Childhood Stunting in Timor-Leste: A Narrative Review - Ivo da Costa Soares; Delmi Sulastri (Jurnal Ners, 2026)
Childhood stunting remains a major public health problem in Timor-Leste, with one of the highest prevalence rates in Southeast Asia. In addition to inadequate nutrition, environmental determinants such as poor sanitation, unsafe drinking water, inadequate hygiene practices, food insecurity, and poor living conditions contribute substantially to impaired child growth and chronic undernutrition. This narrative review aimed to explore and synthesize evidence regarding environmental determinants associated with childhood stunting in Timor-Leste. A narrative review approach was employed using literature obtained from PubMed, Scopus, ScienceDirect, and Google Scholar. Articles published between 2015 and 2025 were screened based on predefined inclusion criteria. Six original studies focusing on environmental determinants of childhood stunting in Timor-Leste were included in the review. Data were synthesized narratively according to major environmental themes. The reviewed studies consistently demonstrated that poor sanitation, unsafe drinking water, food insecurity, household poverty, inadequate housing conditions, and recurrent infectious diseases were major determinants of childhood stunting in Timor-Leste. Children living in rural and socioeconomically disadvantaged households were more vulnerable to chronic undernutrition due to limited access to sanitation, healthcare services, and adequate nutrition. Environmental conditions were also associated with increased exposure to infectious diseases that impair nutrient absorption and child growth. Environmental determinants play a substantial role in the persistence of childhood stunting in Timor-Leste. Addressing stunting therefore requires integrated and multisectoral interventions that combine nutrition-specific programs with environmental health improvements, particularly in water, sanitation, hygiene, food security, and rural health services.